How Can Decentralized Systems Solve System-Level Problems? An Analysis of Market-Driven New Orleans School Reforms. (September 2015) - Buerger, Christian; Harris, Douglas
One of the biggest changes in New Orleans after Katrina was observed in the public school system. In this article, we describe the massive overhaul of the public school system in New Orleans post-Katrina and examine the types of problems that this type of decentralized market-oriented system will be most likely to solve as well as those it may struggle with. As examples, we use problems facing New Orleans public schools, namely, student discipline, information sharing with parents, and especially the human capital pipeline, to illustrate the challenges a regulated market system presents. We then present and apply to those cases a general framework for thinking about which of these types of problems a decentralized system will be best able to solve.